Strategi Majelis Jemaat Untuk Menumbuhkan Iman Jemaat di Jemaat Persiapan Koinonia Lontio - Noveria Halumudala; Naftali Kiyuk; Mardian Baali (TEVUNAH: Jurnal Teologi dan Pendidikan Kristen, 2023)
In pioneering or preparatory congregations of new congregation members, efforts are needed to grow their faith. This research aims to explore the mentoring strategies carried out by the Congregation Council to develop the faith of the congregation at the Christian Church in Luwuk Banggai (GKLB) Koinonia Lontio Preparatory Congregation in Kabua-Bua village, Nuhon sub-district, Banggai district, Central Sulawesi. The research methodology used in this research is qualitative research with a case study approach. The data collection technique used is interviews, and data analysis techniques are reduction, display, and verification. The results of this research indicate that pastoral care is an effective strategy for growing congregational faith. Pastoral care is carried out through pastoral conversations, visits to congregation homes, and assistance in difficult times. The growth of faith can be seen in the members of the congregation who were previously not active in worshiping, becoming diligent in worshiping and willing to participate in worship activities.